Procalcitonin Serum Level in the Admitted COVID-19 Patients - Somayeh Sheidaei; Maryam Ghasemi; Elahe Kavoosi; Fatemeh Abedian Kenari (Mazandaran University of Medical Sciences, 2023)
Background: Coronavirus disease 2019 (COVID-19) is an emerging disease that has affected the world and requires extensive studies. Studies have shown that high procalcitonin (PCT) level is associated with the severity of many diseases, such as bacterial endocarditis, pancreatitis, pyelonephritis, enterocolitis, and even appendicitis. This study aimed to evaluate the serum PCT levels in COVID-19 patients admitted to hospitals in northern Iran. Methods: This cross-sectional descriptive-analytical study was conducted in Boo-Ali Sina and Imam Khomeini hospitals, Mazandaran Province, the north of Iran. A questionnaire consisting of demographic characterization was filled out for every patient. Results of some laboratories and clinical manifestations of the disorder were extracted from their clinical records. Results: A total of 103 COVID-19 patients (53 male and 50 female) were included in the study. Our patients' mean serum PCT level was 0.18±0.024 ng/mL. Significant relationships existed between patients' age and serum PCT level (P=0.025) and short-term prognosis (P=0.044). Conclusion: The short-term prognosis of the disease was significantly associated with the serum PCT level, which indicates that increasing the serum PCT levels worsen the short-term prognosis. Therefore, serum PCT level may help determine disease severity and predict the prognosis of the disease in COVID-19 patients.